Pengaruh Likuiditas, Modal Kerja, dan Efisiensi terhadap Kinerja Keuangan dengan Variabel Kontrol SIZE, LEV, AGE, dan FGR pada Perusahaan Makanan dan Minuman di BEI (2019–2023) - Nugrahani, Catur; Harun, Paulina (STIE Indonesia Banking School, 2025)
This study aims to analyze the effect of Liquidity, Net Working Capital, and Firm Efficiency on financial performance measured by Return on Assets (ROA) in food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The control variables include Firm Size, Financial Leverage, Firm Age, and Growth Rate. The sample consists of 55 companies selected through purposive sampling based on the completeness of financial reports and the presentation of data in Rupiah. The analysis was conducted using panel data–based multiple linear regression. The results show that Current Ratio, Net Working Capital, and Total Asset Turnover have a significant positive effect on ROA. Conversely, Firm Size and Financial Leverage have a significant negative effect, while Firm Age and Growth Rate do not exhibit a meaningful influence. These findings highlight the importance of managing liquidity, working capital, and asset efficiency. For future research, it is recommended to expand the scope to other industrial sectors for more generalizable results, include alternative performance indicators such as ROE, and incorporate external variables such as market risk and economic conditions to provide a more comprehensive understanding.